Question
upstudy study bank question image url

Write the first five terms of the sequence. \( f(0)=-7, f(n)=3 f(n-1) \) \( f(0)=6, f(n)=-2 f(n-1) \)

Ask by Washington Deleon. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

First five terms of the first sequence: -7, -21, -63, -189, -567 First five terms of the second sequence: 6, -12, 24, -48, 96

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Beyond the Answer

Let's break down both sequences one by one! For the first sequence: - \( f(0) = -7 \) - \( f(1) = 3 \cdot f(0) = 3 \cdot (-7) = -21 \) - \( f(2) = 3 \cdot f(1) = 3 \cdot (-21) = -63 \) - \( f(3) = 3 \cdot f(2) = 3 \cdot (-63) = -189 \) - \( f(4) = 3 \cdot f(3) = 3 \cdot (-189) = -567 \) So the first five terms are: \(-7, -21, -63, -189, -567\). Now for the second sequence: - \( f(0) = 6 \) - \( f(1) = -2 \cdot f(0) = -2 \cdot 6 = -12 \) - \( f(2) = -2 \cdot f(1) = -2 \cdot (-12) = 24 \) - \( f(3) = -2 \cdot f(2) = -2 \cdot 24 = -48 \) - \( f(4) = -2 \cdot f(3) = -2 \cdot (-48) = 96 \) Thus, the first five terms are: \(6, -12, 24, -48, 96\).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy